O PRONAF nos municípios de Caiuá e Teodoro Sampaio - SP - Carmo, Janio Gomes do [UNESP] (2015)
The present research had focused on the analysis of the role exercised by National Programme for Strengthening Family Agriculture (PRONAF) in Teodoro Sampaio's and Caiuá's rural settlements. From the 1990's, there was official recognition as family farmers by official agencies, in this way, federal funds were directed to this category. The participation of social movements was extremely important for the recognition of family farmers and implementation of PRONAF. This program has provided access to the resources intended for the costing of harvests and the making of investments at affordable interest to distinct beneficiaries. Even so, there was low volume of funds directed to settled farmers. These farm workers have difficulties to access the PRONAF's funds, due to low incomes obtained in lots, reduced insertion, formal economy, and low social organization. For settled farmers in Caiuá and Teodoro Sampaio, the agricultural credit guarantees the financing of production and achievement of first investments which allow the structuring of production units and, consequently, the expansion of the income derived from the exploitation of lots. This income is reversed on purchase of products of all kinds in the local market, especially those linked to agriculture. However, some settled farmers haven't been able to pay off PRONAF's tranches due to low production and difficulties of marketing of agricultural products